Richard Leplastrier : Spirit of Nature Wood Architecture Award 2004 - Neuvonen, Petri; Lehtimäki, Kristiina (Rakennustieto, 2004)
Featuring eight of his Australian projects dating from 1974 to 2000, this book includes critiques of his oeuvre from Gunnel Adlercreutz and Peter Stutchbury, as well as from the artist himself.